Static and active tactile perception and touch anisotropy: aging and gender effect - A. Abdouni (Nature Portfolio, 2018)
Abstract Although the human finger is the interface used for the touch process, very few studies have used its properties to provide a description of tactile perception regarding age and gender effects. Age and gender effects on the biophysical properties of the human finger were the main topics of our previous study. Correlating tactile perception with each parameter proved very complex. We expand on that work to assess the static and dynamic touch in addition to the touch gestures. We also investigate the age and gender effects on tactile perception by studying the finger size and the real contact area (static and dynamic) of forty human fingers of different ages and gender. The size of the finger and the real contact area (static and dynamic) define the density of the mechanoreceptors. This density is an image of the number of mechanoreceptors solicited and therefore of tactile perception (static and dynamic). In addition, the touch gestures used to perceive an object’s properties differ among people. Therefore, we seek to comprehend the tactile perception of different touch gestures due to the anisotropy of mechanical properties, and we study two different directions (top to bottom and left to right).